Tax policies and developing countries - International Chamber of Commerce. Commission on Taxation (International Chamber of Commerce., Paris., 1970)
This book is for financing countries should recognize thatbthere is a place for both the exemption method and the tax credit method of relief in their tax system.
aia 06/03/2019
Loans
Keywords: Taxation; Developing Countries